Configuration predictions of large liquefied petroleum gas (LPG) pool fires using CFD method. (May 2020) - Yi, Hang; Feng, Yu; Park, Haejun; Wang, Qingsheng
Abstract: Liquefied petroleum gas (LPG) has potential pool fire risks due to its flammability. The configuration of pool fires plays a significant role when applying the solid flame model or point source model to assess the risks from heat radiation. However, no existing correlations can precisely predict the configuration of large LPG (100% propane) pool fires. To enhance the fundamental understanding on how pool diameter and wind velocity can influence the configuration of large LPG pool fires, an experimentally validated Computational Fluid Dynamics (CFD) model is employed to simulate fires using different burning rate models. Fire temperature profiles, flame heights, and flame tilts predicted by the CFD model were compared with empirical models and experimental data. Accordingly, new correlations for flame height and flame tilt as functions of pool diameter D and wind velocity u w have been developed. The comparisons demonstrate that the new correlations have the best overall accuracy in the prediction of flame height and tilt for large LPG pool fires under different conditions (10 m ≤ D ≤ 20 m, 0 ≤ u w ≤ 3 m·s −1 ). Highlights: LPG pool fire configuration was studied by using CFD method. New correlations were developed to predict the configuration behaviors of large LPG pool fires. Fire configuration influences by pool diameter and wind velocity were discussed. An experimentally validated CFD model was employed to simulate pool fires.